The influence of height on the spreading distance of axisymmetric jets impinging on a rigid surface - Luthfi Luthfi (Jurnal POLIMESIN, 2022)
The influence of the domain height of negative buoyancy jets when impinging on a rigid surface has been investigated. The study was conducted numerically by applying the Computational Fluid Dynamics (CFD) method.  The numerical model consists of a set of Navier-Stokes equations together with an energy equation. The jet flow was modeled in a two-dimensional axisymmetric coordinate. The governing equations were solved in transient using the finite volume approach. The programming code for the numerical model was written in Fortran. The numerical simulations were run at Froude number Fr = 5.0; Reynolds number, Re = 200 and Prandtl number Pr = 7.0. The investigated parameter, the domain height was varied at around 8.8 ≤ H/X0 ≤ 10.2. The flow visualization created from simulation results has revealed the mystery behind the complex flow behavior in detail. Starting from the initial flow when the jet entered the domain to the complex flow pattern of the jet flow detaching from the top surface. Including when the downflow mixes with the upflow creating a recirculation area near the top surface and the bottom of the domain. The plot of the spreading distance over time shows that there is a maximum distance when the jet starts detaching from the top surface. Gradually, the distance decreases until reaching a fixed final distance when the jet flow reaches quasi-steady. The influence of the domain height that was investigated shows different flow patterns at different heights. The plot of final distances over the domain height shows that there is a nonlinear relationship. The regression equation created from the numerical data shows good agreement and accuracy.